Transforming several models as minimum cost capacitated (MCF) - 494400 Diyana Abd. Mahad @ Abdul Hamid; Siti Roslindar Yaziz; Fakulti Sains (2007)
Project Paper (Sarjana Muda Sains serta Pendidikan (Matematik)) - Universiti Teknologi Malaysia, 2007